Experience on the use of Chinese herbal medicine in the control of chemotherapy side effects among thyroid cancer patients in Bao Tou City, Mongolia - Wang, Huming
This study aimed to determine the effectiveness of the use of Chinese herbal medicine to control the side-effects of chemotherapy among patients with thyroid cancer patients managed in four hospitals in Bao Tou City, Mongolia in a prospective cohort study. Thirty female patients were included in the final sample.Patients were alternately assigned to intervention and control groups after they were referred to the study by the four oncology centers: ErJi, YiFi, and ErFu Hospitals in Bao Tou City, Mongolia. All patients received chemotherapy (2 to 3-drug regimens of either 50-fluouracil, cyclophosphamide, mitoxantron, doxorubicin and/or methotrexate) and anti-emetic drugs (either metoclopramide, ondansetron, or tropisetron). The intervention group received Chinese herbal medicine in addition to all the medication given to the subjects in the control group.